2009
DOI: 10.1007/s10059-009-0069-0
|View full text |Cite
|
Sign up to set email alerts
|

Basement Membrane Proteoglycans: Modulators Par Excellence of Cancer Growth and Angiogenesis

Abstract: Proteoglycans located in basement membranes, the nanostructures underling epithelial and endothelial layers, are unique in several respects. They are usually large, elongated molecules with a collage of domains that share structural and functional homology with numerous extracellular matrix proteins, growth factors and surface receptors. They mainly carry heparan sulfate side chains and these contribute not only to storing and preserving the biological activity of various heparan sulfate-binding cytokines and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
203
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(208 citation statements)
references
References 131 publications
1
203
0
4
Order By: Relevance
“…Urine proteomic analysis identified LG3 as a novel biomarker of CTV in renal transplant recipients [30,31,58]. The present work demonstrates that LG3 could participate in the pathophysiology of CTV through inhibition of apoptotic pathways in hMSC.…”
Section: Discussionmentioning
confidence: 59%
“…Urine proteomic analysis identified LG3 as a novel biomarker of CTV in renal transplant recipients [30,31,58]. The present work demonstrates that LG3 could participate in the pathophysiology of CTV through inhibition of apoptotic pathways in hMSC.…”
Section: Discussionmentioning
confidence: 59%
“…The heparan sulfate proteoglycans agrin, perlecan, and type XVIII collagen have the potential to tether and accumulate growth factors (Iozzo et al 2009). Such heparin-binding factors include fibroblast growth factors (FGF, especially FGF-2), transforming growth factor-b (TGFb-1,2), bone morphogenic proteins (BMPs-2,4,7), glial-derived neurotrophic factor (GDNF), vascular endothelial growth factors (VEGF), heparin-binding epidermal growth factor (HB-EGF), and neuregulin (Plotnikov et al 1999;Li and Loeb 2001;Rider 2006).…”
Section: Proteoglycans and Growth Factor Tetheringmentioning
confidence: 99%
“…We found that one tryptic peptide that matched to perlecan by MS/MS, as well as PMF, resided on the C-terminal domain V of perlecan, commonly known as endorepellin (Table 2). Endorepellin blocks endothelial cell migration and capillary morphogenesis, both in vitro and in vivo [26]. Endorepellin interacts specifically with the α2β1 integrin [27], and stimulation with endorepellin induces the interaction and phosphorylation of Src homology-2 protein phosphatase-1 with integrin α2 in endothelial cells [28].…”
Section: Discussionmentioning
confidence: 99%